Analysis of the state of creation of robotic complexes for humanitarian demining - Nevliudov, Igor; Yanushkevych, Dmytro; Ivanov, Leonid (Technology audit and production reserves, 2021)
The object of research is robotic military complexes used in the system of humanitarian demining. This work aims to study the requirements for robotic military complexes (including manipulators that are sucked into them) and to develop proposals for their use in humanitarian demining. The research is based on the application of a functional approach to the construction of models for the formation of requirements for robotic military complexes (RMC), which are sucked into the system of humanitarian demining. It is established that the creation of RMC requires a significant study of the core of the most important technologies that are needed to create the entire range of promising RMC. Thus the standard sample RMC can be presented in the form of set of functionally connected elements: the basic carrier, the mobile platform, the specialized hinged/built-in equipment in the form of a set of removable modules of useful (target) purpose, means of maintenance and service used at preparation for application and technical operation robot. The composition of specialized equipment is set based on the functional purpose of the RMC. The classification of RMC is given, which provides for their division into three categories: the first generation – controlled devices, the second generation – semi-autonomous devices and the third generation – autonomous devices. The analysis of modern RMC which are developed in Ukraine and the advanced countries of the world and the analysis of structure of components of system of humanitarian demining is carried out. It is established that the organization of the humanitarian demining system with the use of RMC should include of explosive objects (EO) reconnaissance, search, marking, their identification and direct demining. Unmasking signs of EO, as well as modern methods and detectors of EO detection are considered. One of the new promising methods of mine detection is parametric. However, in real application, the most promising is the use of a combination of electromagnetic, optical and mechanical methods. The application of the proposed approaches will increase the efficiency of humanitarian demining and reduce human losses in its implementation.